Pengaruh Ramipril Terhadap Gambaran Histopatologis Otak Tikus Wistar yang Mengalami Edema Otak - Rizka Fitria Husni; Nita Afriani; Aswiyanti Asri (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Brain edema is excessive accumulation of fluid in the intracranial or extracellular space of the brain. It can be caused by head trauma, brain tumors, hypoxia, metabolic disorders, or acute hypertension. Acute myocardial infraction is damage to the myocard that occurs due to lack oxygen. When acute myocardial infarction occurs, there will be disruption of blood flow in the form of stasis which allows emboli and decreased Cardiac Output which will cause a decrease in Cerebral Blood Flow. There will be a state of ischemia and hypoxia so that the hemostatic mechanism is disturbed which will trigger brain edema. Objective. This research was conducted to see the effect of giving ramipril to histopathological of the brain of wistar rat with brain edema. Methods. This research is an experimental study. We used 32 animals which were divided into 4 groups (K-, K +, P1, and P2). P1 was given 3 mg/kgBW ramipril for 7 consecutive days. P2 was given 4 mg/kgBW ramipril for 7 consecutive days. On days 8 and 9, P1, P2, and K+ induced isoproterenol 85 mg/kgBW for 2 consecutive days to induce brain edema through the mechanism of acute myocardial infarction. Data analysis was performed using One Way Anova test and Post Hoc Bonferroni test. Results. The mean area of ​​brain edema in the K-, K +, P1, and P2 groups respectively were 20.76%, 34.69%, 22.70%, and 21.90%. Conclusion. There was a significant effect of giving ramipril to histopathological of the brain of wistar rat with brain edema